Using single top rapidity to measure V-td, V-ts, V-tb at hadron colliders - Aguilar-Saavedra, J. A. (2011)
Single top production processes are usually regarded as the ones in which V-tb can be directly measured at hadron colliders. We show that the analysis of the single top rapidity distribution in t-channel and tW production can also set direct limits on V-td. At LHC with 10 fb(-1) at 14 TeV, the combined limits on V-td may be reduced by almost a factor of 2 when the top rapidity distribution is used. This also implies that the limits on V-tb can also be reduced by 15%, since both parameters, as well as V-ts, must be simultaneously obtained from a global fit to data. At Tevatron, the exploitation of this distribution would require very high statistics.